The association between dietary acid load and odds of prostate cancer: a case-control study - Sanaz Mehranfar; Yahya Jalilpiran; Haleh Rahimi; Alireza Jafari; Leila Setayesh; Cain C. T. Clark; Shiva Faghih (Journal of Health, Population and Nutrition)
Abstract Background and objective Conflicting results exist regarding the associations between dietary acid load (DAL) and cancer risk. This study aimed to investigate the association between DAL and the odds of prostate cancer (PC) in the Iranian population. Methods One hundred and twenty participants (60 controls and 60 newly diagnosed PC patients) engaged in a hospital-based case-control study conducted from April to September 2015. A validated, 160-item semi-quantitative food frequency questionnaire (FFQ) was used to assess usual dietary intakes. DAL was calculated using potential renal acid load (PRAL) and net endogenous acid production (NEAP). Multivariate logistic regression was performed to estimate odds ratios (ORs). Results Both PRAL (OR = 5.44; 95% CI = 2.09–14.17) and NEAP (OR = 4.88; 95% CI = 2.22–13.41) were associated with increased odds of PC in the crude model. After adjusting for potential confounders (energy intake, smoking, physical activity, ethnicity, job, education, and medication use), being in the third category of PRAL (OR = 3.42; 95% CI = 1.11–8.65) and NEAP (OR = 3.88; 95% CI = 1.26–9.55) were significantly associated with increased odds of PC. Conclusion Our findings suggest that dietary acid load may be linked to an increased risk of PC; however, further prospective studies with larger sample sizes and longer durations are necessary to validate these findings.